2023
DOI: 10.3390/plants12132413
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Alleviates Cadmium Stress by Enhancing Photosynthetic Efficiency and Regulating Sugar Metabolism in Wheat Seedlings

Abstract: Hydrogen sulfide (H2S) plays prominent multifunctional roles in the mediation of various physiological processes and stress responses to plants. In this study, hydroponic experiments were carried out to explore the effects of NaHS pretreatment on the growth of wheat (Triticum aestivum L.) under 50 μM cadmium (Cd). Compared with Cd treatment alone, 50 μM NaHS pretreatment increased the plant height, soluble sugar content of shoots and roots, and dry weight of shoots and roots under Cd stress, while the Cd conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The results are similar to the findings of Altaf et al 43 and Kaya et al, 18 where the authors observed an increase in biomass in response to the individual applications of MLT or H 2 S. Similarly, the application of MLT and H 2 S is reported to enhance the growth of plants grown under Cd stress condition. 44 , 45 The improvement in the plant biomass in response to the application of H 2 S and MLT is strongly linked with the antioxidative ability of MLT and the unique properties of H 2 S.…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to the findings of Altaf et al 43 and Kaya et al, 18 where the authors observed an increase in biomass in response to the individual applications of MLT or H 2 S. Similarly, the application of MLT and H 2 S is reported to enhance the growth of plants grown under Cd stress condition. 44 , 45 The improvement in the plant biomass in response to the application of H 2 S and MLT is strongly linked with the antioxidative ability of MLT and the unique properties of H 2 S.…”
Section: Discussionmentioning
confidence: 99%